2002
DOI: 10.1063/1.1490410
|View full text |Cite
|
Sign up to set email alerts
|

Viscous flow reactor with quartz crystal microbalance for thin film growth by atomic layer deposition

Abstract: A chemical reactor was constructed for growing thin films using atomic layer deposition (ALD) techniques. This reactor utilizes a viscous flow of inert carrier gas to transport the reactants to the sample substrates and to sweep the unused reactants and reaction products out of the reaction zone. A gas pulse switching method is employed for introducing the reactants. An in situ quartz crystal microbalance (QCM) in the reaction zone is used for monitoring the ALD film growth. By modifying a commercially availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
612
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 545 publications
(637 citation statements)
references
References 26 publications
23
612
2
Order By: Relevance
“…The ALD chamber is a viscous flow reactor with the ALD source handling similar to that previously described by Elam et al 29 However, our ALD chamber differs significantly from those previous reported in its dimensions, sample mounting, It is quickly brought between atmospheric pressure and high vacuum by a turbomolecular pump. The ALD chamber (c) is isolated from the other chambers by two gate valves to ensure a proper flow profile of the ALD sources, and it is heated by heat rope wrapped around its exterior (not shown).…”
Section: B Ald Chambermentioning
confidence: 80%
“…The ALD chamber is a viscous flow reactor with the ALD source handling similar to that previously described by Elam et al 29 However, our ALD chamber differs significantly from those previous reported in its dimensions, sample mounting, It is quickly brought between atmospheric pressure and high vacuum by a turbomolecular pump. The ALD chamber (c) is isolated from the other chambers by two gate valves to ensure a proper flow profile of the ALD sources, and it is heated by heat rope wrapped around its exterior (not shown).…”
Section: B Ald Chambermentioning
confidence: 80%
“…Metal oxides were deposited on catalysts using a viscous flow ALD reactor 13 at 1 Torr pressure using ultrahigh purity nitrogen carrier gas at a mass flow rate of 20 sccm and a temperature of 125°C. The catalyst was first heated to 250 o C for one hour to remove physisorbed water and then weighed dry prior to loading into the ALD reactor.…”
Section: Ald Reactant Exposure Time Determinationmentioning
confidence: 99%
“…These results indicate that highly upgraded recycle lube oils can be produced using ALD-deposited active metal catalysts. The use of H 1 and C 13 NMR for the characterization of the treated lube oils has been shown to be effective. …”
mentioning
confidence: 99%
“…For these reasons, the following sections will highlight efforts to control the nanoparticle size, and in particular to achieve ultra-small (<1nm) noble metal nanoparticles. In addition to depositing simple binary compounds such as Al 2 O 3 and elements such as Pd, ALD can also synthesize ternary and more complex compounds such as ZnAl 2 O 4 8 , as well as mixed metals such as Pt-Ir 9 . The ALD of mixed materials is accomplished by alternating between the binary reaction sequences of the individual components in the mixture, and the composition is controlled by adjusting the ratio of ALD cycles for the different components.…”
Section: Introductionmentioning
confidence: 99%
“…ALD reactors typically incorporate a chamber heated to ~100-400°C containing the substrate to be coated 4 . A constant stream of inert gas such as N 2 flows through the chamber at a pressure of ~0.1-10 Torr.…”
Section: Introductionmentioning
confidence: 99%